"I Don't Want Everybody to Vote": Christian Nationalism and Restricting Voter Access in the United States. Issue 1 (3rd January 2022) - Perry, Samuel L.; Whitehead, Andrew L.; Grubbs, Joshua B.
Abstract : Though the persistence of voter suppression and disenfranchisement in the US is well‐documented, we still know little about their contemporary ideological underpinnings beyond partisanship and racial resentment. Highlighting the Christian Right's influence in driving anti‐democratic sentiment in the post‐Civil Rights era, we propose contemporary ideological support for restricting the vote generally, and specifically, to those who prove "worthy, " is undergirded by a pervasive ideology that cloaks authoritarian ethno‐traditionalism with the ultimacy and polysemic utility of religious language―Christian nationalism. Nationally representative data collected weeks before the November 2020 elections reveal Christian nationalism is a leading predictor that Americans deny that voter suppression is a problem, believe that the US makes it "too easy to vote, " believe that voter fraud is rampant, and support measures to disenfranchise individuals who could not pass a basic civics test or who committed certain crimes. Interactions show Christian nationalism's influence is particularly strong among men across most outcomes and, regarding voter suppression, whites compared to Blacks. We argue Christian nationalism seeks to institutionalize founding ideals in which civic participation is rooted in hierarchies, being restricted to a "worthy" few. Appeals to America's religious heritage thus facilitate stratifying America's citizenry and justifying restricting participation to preserve dominance.